Analisis Kemampuan Komunikasi Matematis Siswa SMP Ditinjau Berdasarkan Gender Pada Materi Segiempat - Salsabila, An nisaa Mutiara; Hidayati, Nita (Radian Journal: Research and Review in Mathematics Education, 2024)
This research aims to analyze students' mathematical communication skills in terms of gender differences in quadrilateral material. The type of research used is descriptive qualitative research. The subjects in this study were ninth grade students of Widya Nusantara Junior High School totaling 22 students. To measure students' mathematical communication skills, researchers used test instruments in the form of 3 quadrilateral material description questions which contained 3 indicators of mathematical communication skills and interviews which were then analyzed by the mean difference test. The results of this study show that, in the indicator of mathematical expression, male students tend to create mathematical models based on their understanding without relying on the formulas they have learned. In contrast, female students more often create mathematical models relying on the formulas they have learned. Regarding the drawing indicator, there is no significant difference between the mathematical drawing abilities of male and female students. However, in this indicator, female students excel more than male students. Keywords: Gender, Mathematical Communication Skills, Quadrilateral